A Problem Based Learning Management System: Enhancing Learning Motivation and Academic Achievement in Digital Learning Environments - Rahmat Rizal; Endang Surahman; Haji Aripin; Ernita Susanti; Surya Gumilar (Indonesian Educational Research Journal, 2026)
The integration of Learning Management Systems (LMS) into digital learning environments often remains content-focused and fails to foster active student engagement, resulting in low motivation and suboptimal academic achievement. This study aims to examine the effect of a Problem-Based Learning Management System (PBLMS) on students' learning motivation and academic achievement, both separately and simultaneously. A quasi-experimental design with a pretest–posttest non-equivalent control group was employed, involving 64 undergraduate students in physics education. The experimental group was taught using PBLMS, while the control group used a conventional LMS (Google Classroom) with direct instruction. Data were collected using a validated motivation questionnaire based on the ARCS model and an academic achievement test covering cognitive levels C1–C5. Data analysis included N-Gain, ANCOVA, and MANCOVA tests. The results revealed that the experimental group achieved significantly greater improvements in both learning motivation (N-Gain = 0.88, high category) and academic achievement (N-Gain = 0.86, high category) than the control group (0.48 and 0.60, moderate category, respectively). ANCOVA results confirmed a significant effect of PBLMS on both variables (p < 0.05), while MANCOVA indicated a significant simultaneous effect. The findings suggest that integrating problem-based learning within an LMS creates a more interactive, student-centered, and meaningful learning environment that enhances both learning motivation and academic achievement. This study bridges the gap between pedagogical models and digital technology by proposing PBLMS as an effective framework for improving motivation and academic performance in higher education